2019
DOI: 10.1038/s41598-018-37192-4
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Transgenesis in Ferrets Using CRISPR/Cas9-Mediated Homology-Independent Insertion at the ROSA26 Locus

Abstract: The domestic ferret (Mustela putorius furo) has proven to be a useful species for modeling human genetic and infectious diseases of the lung and brain. However, biomedical research in ferrets has been hindered by the lack of rapid and cost-effective methods for genome engineering. Here, we utilized CRISPR/Cas9-mediated, homology-independent insertion at the ROSA26 “safe harbor” locus in ferret zygotes and created transgenic animals expressing a dual-fluorescent Cre-reporter system flanked by PhiC31 and Bxb1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…Fifth, transgenic ferrets are now available ( Johnson et al, 2018 ; Yu et al, 2019 ). Moreover [combining the steps 6–9 from Matthews and Vosshall (2020) ] genome editing ( Shinmyo et al, 2017 ), routine gene knock-down ( Kostic et al, 2019 ) and knock-out ( Güven et al, 2020 ; Xing et al, 2020 ), introduction of precise mutation ( Yu et al, 2019 ), optogenetics ( Roy et al, 2016 ) and other genetic tools important for neuroscience have all been introduced to the ferrets. Finally, interesting questions that can be addressed using the ferret as the model organism are not lacking and include, but are not limited to, the considerations we discuss below.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifth, transgenic ferrets are now available ( Johnson et al, 2018 ; Yu et al, 2019 ). Moreover [combining the steps 6–9 from Matthews and Vosshall (2020) ] genome editing ( Shinmyo et al, 2017 ), routine gene knock-down ( Kostic et al, 2019 ) and knock-out ( Güven et al, 2020 ; Xing et al, 2020 ), introduction of precise mutation ( Yu et al, 2019 ), optogenetics ( Roy et al, 2016 ) and other genetic tools important for neuroscience have all been introduced to the ferrets. Finally, interesting questions that can be addressed using the ferret as the model organism are not lacking and include, but are not limited to, the considerations we discuss below.…”
Section: Discussionmentioning
confidence: 99%
“…The knockout was achieved by Transcription Activator Like Effector Nucleases (TALEN)-mediated genome editing. A year later, Yu et al (2019) reported the creation of a transgenic ferret line expressing a dual-fluorescent Cre-reporter system inserted into the ferret ROSA26 intron 1. In this case CRISPR/Cas9-based genome editing was employed.…”
Section: Techniques For Functional Studies In Ferretsmentioning
confidence: 99%
See 1 more Smart Citation
“…Often these approaches aim to accomplish specific targeted integration of genes of interest into what is known as safe harbor’ genes, such as Rosa26, adeno-associated virus integration site 1 (AAVS1), and H11 ( Ruan et al, 2015 ; Wu et al, 2016 ; Xie et al, 2017 ). These sites in the genome are able to accommodate the transgene integration that ensures its high transcriptional activity in embryonic and adult tissues, and does not suppress critical endogenous genes ( Ruan et al, 2015 ; Oceguera-Yanez et al, 2016 ; Weber et al, 2016 ; Wu et al, 2016 ; Yu et al, 2019 ; Kelly et al, 2020 ).…”
Section: Improvements Of Crispr/cas9mentioning
confidence: 99%
“…Zygotes ( n = 151) were microinjected with the plasmid and CRISPR/Cas9 RNP. Five out of 23 offspring exhibited the reporter expression ( Yu et al, 2019 ). Therefore, HITI method offers a great enhancement over the other methods as it takes advantage of NHEJ for gene insertion.…”
Section: Improvements Of Crispr/cas9mentioning
confidence: 99%